2010
DOI: 10.1111/j.1440-169x.2010.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of CpG island promoters: A consequence or cause of evolution?

Abstract: CpG islands (CGIs) are CG-rich stretches in the genome that are concentrated near the transcription start sites (TSS) of genes. Genes that possess CGIs, such as the housekeeping genes, are often highly expressed in multiple tissues. Indeed, CGIs are enriched in approximately half of the promoters in humans and mice, suggesting an important role for CpG islands in mammalian transcriptional regulation. Interestingly, accumulation of CpG islands at TSS appears to be a vertebrate specific genomic feature, which im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
3
33
6
Order By: Relevance
“…a different set of genes expressed) for the growth and differentiation of the placenta. In our previous work, we had observed a link between the evolution of placenta and genes that have CpG islands (CGIs) in their promoters [80].…”
Section: Do Iap Insertions Sensitize Host Genes To Environmental Cuesmentioning
confidence: 99%
“…a different set of genes expressed) for the growth and differentiation of the placenta. In our previous work, we had observed a link between the evolution of placenta and genes that have CpG islands (CGIs) in their promoters [80].…”
Section: Do Iap Insertions Sensitize Host Genes To Environmental Cuesmentioning
confidence: 99%
“…In contrast, most mammalian promoters are enriched for GC-rich areas-also called CpG islands (CGIs)-whereas TATA boxes only appear in a minority of genes (Sandelin et al 2007). CGIs are defined as large genomic areas of over-enriched CpG dinucleotides estimated to amount to between 20,000 and 30,000 in various mammalian genomes lacking counterparts in cold blooded organisms or other eukaryotes (Illingworth and Bird 2009;Sharif et al 2010). Although recent works suggest a link between nucleosome depletion at promoters and the presence of CGIs, a direct correlation was never established (Li et al 2011;Valouev et al 2011).…”
mentioning
confidence: 99%
“…This bimodality is also observed in several other vertebrates including humans, chicken, frog and zebrafish [10]. However, the overall percentage of promoters that overlap a CpG island was later shown to be much lower in cold-blooded vertebrates (<20%) when compared to warm-blooded vertebrates (>40%) [11]. This suggested that very few promoters are unmethylated in cold-blooded vertebrates, or that the role of CpG-rich regions may differ between these two groups of organisms.…”
Section: Introductionmentioning
confidence: 73%